2021
DOI: 10.3390/ijms22041853
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli Outer Membrane β-Barrel Assembly Machinery (BAM) Anchors the Peptidoglycan Layer by Spanning It with All Subunits

Abstract: Gram-negative bacteria possess a three-layered envelope composed of an inner membrane, surrounded by a peptidoglycan (PG) layer, enclosed by an outer membrane. The envelope ensures protection against diverse hostile milieus and offers an effective barrier against antibiotics. The layers are connected to each other through many protein interactions. Bacteria evolved sophisticated machineries that maintain the integrity and the functionality of each layer. The β-barrel assembly machinery (BAM), for example, is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 47 publications
0
9
0
3
Order By: Relevance
“…In this study, we revealed the spatiotemporal topography of the BAM complex in E. coli cells, and its dependence on the presence of the Z-ring. The BAM complex localizes all along the cell periphery in distinct foci or clusters, as has been reported before [19][20][21][22]. Here, new insight was gained into the localization of BAM, by studying its cellular distribution during the cell division cycle.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…In this study, we revealed the spatiotemporal topography of the BAM complex in E. coli cells, and its dependence on the presence of the Z-ring. The BAM complex localizes all along the cell periphery in distinct foci or clusters, as has been reported before [19][20][21][22]. Here, new insight was gained into the localization of BAM, by studying its cellular distribution during the cell division cycle.…”
Section: Discussionmentioning
confidence: 59%
“…Analysis of the amount of fluorescence of the labelled BAM per cell divided by the calculated cell volume assuming the cell to have a rod-shape provides the BAM concentration per µm 3 . The BAM complex is continuously produced as its concentration remained quite constant at all cell ages when grown in minimal medium (Figure 1C), as well as in rich medium [22]. Strikingly, the fluorescence demographic map of cells sorted by their length revealed a BAM complex enriched at the site of constriction, in the second half of the cell division cycle (Figure 1B).…”
Section: The Bam Complex Localizes At Midcell During Constrictionmentioning
confidence: 90%
See 2 more Smart Citations
“…1C). The OM pore inserting BAM complex is also not accessible without lysozyme treatment [64]. This suggests that PBP4 resides between the OM and the PG layer.…”
Section: Pbp4 Localizes Between the Peptidoglycan Layer And The Outer Membranementioning
confidence: 97%